Value chain analysis of dairy in Laelay Maychew and Adwa Districts in Central Zone of Tigray, Ethiopia - Tekelyesus, H. (Mekelle University, 2015)
This study was aimed at analyzing dairy value chain in Laelay Maychew and Adwa districts of Tigray Region. The main focus was to describe and characterize different value chain actors, functions and services providers along the dairy value chain, to quantify the economic contribution of dairy value chain to actors and to investigate factors of small holder farmer’s participation in dairy value chain. To accomplish these tasks formal and informal data collection tools for both primary and secondary data. A total of eighty smallholder dairy farmers from Laelay Maychew and eighty smallholder dairy farmers from Adwa district were selected at random and were interviewed using structured questionnaire. Milk and butter were the most important dairy products marketed in the areas. Dairy producers and retailers (café and restaurants) are found to be important milk market chain actors in the study area. From the milk value chain actors, 66.5% of retailers (café and restaurants) and 33.5% of milk producers added a value to the milk. In milk market, milk retailers enjoyed the highest net profit. The econometric estimation procedure was employed to identify factors that determine milk market participation decision and milk sale volume of the farm household in the area. The logistic regression results showed that educational level, cross breed type, access to credit and access to extension service are significantly affecting milk market participation decision. Similarly estimation results of second stage Heckman selection model showed that breed type and total milk product were significantly affecting volume of milk supply. The major constraints of dairy production and marketing in the studied areas were inadequate availability and supply of feed, low volume of milk, lack of training access, low house hold income/low purchasing power, unavailability of cooling facilities for milk storing, distance to market, low market demand of the product, low breed performance, access to transport, land access, access to water. Dairy product value chain in the study area seemed to be ineffective and underdeveloped. Thus, dairy development interventions should be aimed at addressing both dairy production technological gaps and marketing problems. The study further suggested strengthening of dairy cooperatives and milk processing industries establishment, improving access to services and consolidating the linkage among dairy value chain actors should receive due attention in order to improve dairy production and marketing.